Issues in Internationalization of education: The case of a Danish Business School exporting a blended learning MBA program to developing countries - Fahmy, Sandra Safwat; Bygholm, Ann; Jaeger, Kirsten (Proceedings of the International Conference on Networked Learning, 2012)
Internationalization activities, according to Roger Bennett (Bennett and Kane 2009) include, but are not limited to, international franchising, curriculum internationalization, exchange programs, and the recruitment of foreign teaching staff. Internationalization also includes cross-border delivery of educational services, for example in the form of net-based distance education or blended learning programs (Hughes 2008). This paper addresses the issues that an educational institute may face when offering blended learning programs in countries, in which the cultural and social context, the educational and pedagogical traditions, and the access to supporting technologies differ markedly from the corresponding conditions in its home country. Based on the insights emerging from a discussion of these issues, the paper points out the problem areas in which further research is needed in order to establish a theoretical and practical platform for cross-cultural delivery of higher education as blended-learning programs. In theory, there seems to be a perfect fit between the principles of blended learning and the needs of both the provider of cross-border higher education and the students. Within a blended learning framework, it should be possible to achieve the fine balance between exposure to high quality learning material, well-qualified teachers and face-to-face interaction in local learning environments. However, concrete experience made by a Danish higher education provider when offering an MBA education as a blended learning program in Egypt and Vietnam strongly indicates the pedagogical, organizational, social and cultural complexity involved in such an endeavour and the need to further develop blended-learning methods. The case of a Danish private business school "International Business School of Scandinavia" (IBSS) and its experience in exporting a blended learning MBA program designed in Denmark to countries in the Middle East and Asia show that the use of the blended learning mode of teaching and advanced distance learning technologies was not enough to overcome the barriers that arise in countries which in significant ways differ from the program’s country of origin. Within the overall framework of internationalization of education and blended learning theory, this paper accounts for the obstacles met by the Danish MBA provider and discusses how these experiences challenge state-of-the-art theory and practice in the area of blended learning.